¿Amistad excepcional? Pensar las relaciones musicales entre Chile, Cuba y Uruguay (1967-1973) - Javier Rodríguez Aedo (Caravelle)
With a gap of a few years, popular and folk musicians from Latin America tried to meet other audiences, developing international tours and a musical work closely related to musical diplomacy. Simultaneously, its local music scenes expanded and consolidated, successfully promoting the arrival of sounds from Latin America, the Soviet countryside, and Africa. This article addresses the musical and political relationships between Chilean, Cuban, and Uruguayan artists, developed within the framework of the dynamics of the internationalization of political song, underway at the end of the 1960s.